PENGARUH KOMITMEN ORGANISASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Mahardita, Elisya Jauhar; Noermijati, Noermijati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The success of an organization can be determined by many variables, one of which is its human resource. To achieve success, organizations need employees who are willing to take tasks not listed on their job description and those that surpass the expectation of their organization, which is termed as organizational citizenship behavior (OCB). The goal of this study is to analyze the effect of organizational commitment on organizational citizenship behavior at PG Kebon Agung Malang. The independent variables of this research are affective commitment, continuance commitment, and normative commitment, while the dependent variable is organizational citizenship behavior (OCB). The population of this quantitative explanatory research is 252 permanent employees of PG Kebon Agung Malang. Using probability sampling, 155 people were selected as the sample. The results of the descriptive and multiple linear regression analysis have led to findings that affective commitment and normative commitment has significant effect on organizational citizenship behavior (OCB), while continuance commitment has no significant effect on organizational citizenship behavior (OCB).